Using a haptic device and virtual sculpting software for predicting a missing mandible: the case of Angelo Poliziano (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2012)
-
Keywords: forensic; anthropology; virtual; reconstruction